THE KESH OASIS WITHIN THE SYSTEM OF SOUTHERN SOGD: POPULATION SEDENTARIZATION, TRADE, AND POLITICAL PROCESSES (6TH–8TH CENTURIES) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article provides a scholarly analysis of the processes of population sedentarization in the territory of Southern Sogd, the historical and geographical position of the Kesh oasis, and its significance in the political, economic, and cultural life of the region during the sixth to eighth centuries. Based on data from ancient Chinese chronicles, Turkic and Islamic written sources, as well as the results of archaeological research, the study examines the features of the confederative political structure of Sogd, the leading role of the Sogdians along the Great Silk Road, and their political, economic, and cultural interactions with Turkic tribes.